SPECIFICITY OF MODERN BELARUSIAN SOCIETY STRATIFICATION: REGIONAL PECULIARITUES - V. A. Klimenko; I. V. Lashouk (Наука и техника)
The paper considers main approaches to the investigation of a social stratification which  exists in a modern scientific tradition. Methodology has been developed and proposed on the basis of  investigations executed in monitoring regime by the Institute of Sociology of the National Academy of Sciences of Belarus. The methodology makes it possible to set out a stratification of the Belarusian society with due account of consumer needs, possibilities and level of deprivation. The paper presents an economical structure of the Belarusian society as a whole. Regional peculiarities of the stratification in view of a settlement type have been analyzed in the paper as well.